2012
DOI: 10.1186/1471-2180-12-64
|View full text |Cite
|
Sign up to set email alerts
|

Clonal complexes and virulence factors of Staphylococcus aureus from several cities in India

Abstract: BackgroundDiseases from Staphylococcus aureus are a major problem in Indian hospitals and recent studies point to infiltration of community associated methicillin resistant S. aureus (CA-MRSA) into hospitals. Although CA-MRSA are genetically different from nosocomial MRSA, the distinction between the two groups is blurring as CA-MRSA are showing multidrug resistance and are endemic in many hospitals. Our survey of samples collected from Indian hospitals between 2004 and 2006 had shown mainly hospital associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 34 publications
8
69
3
Order By: Relevance
“…Further, a recent study in rural India has identified MRSA as replacing MSSA in causing many community-acquired soft-tissue infections, being responsible for 64.7% of community-acquired S. aureus infections in the series described [13]. One can only speculate about the significance of the insect bites in the current case, and, of note, the dominant sequence types identified in India have been ST22 and ST772, which are different from the organism identified here, although 69% PVL positivity is identified among strains in India [14]. The strain of MRSA described in our case report was characterized by spa typing (using the polymorphous X region of the protein A gene) rather than multilocus sequence typing, but spa t021 has been shown to correspond with ST030 on multilocus sequence typing [15].…”
Section: Discussioncontrasting
confidence: 61%
“…Further, a recent study in rural India has identified MRSA as replacing MSSA in causing many community-acquired soft-tissue infections, being responsible for 64.7% of community-acquired S. aureus infections in the series described [13]. One can only speculate about the significance of the insect bites in the current case, and, of note, the dominant sequence types identified in India have been ST22 and ST772, which are different from the organism identified here, although 69% PVL positivity is identified among strains in India [14]. The strain of MRSA described in our case report was characterized by spa typing (using the polymorphous X region of the protein A gene) rather than multilocus sequence typing, but spa t021 has been shown to correspond with ST030 on multilocus sequence typing [15].…”
Section: Discussioncontrasting
confidence: 61%
“…USA400 appears to be more virulent than USA300 [6 ], but is rarely isolated in the U.S. outside of the aforementioned regions. In recent years, ST772-V (Bengal Bay clone), a single locus variant of ST1 (differing by a single MLST allele), has emerged as a virulent and unusually resistant CA-MRSA strain in Bangladesh and India [31], and is increasingly reported in the U.K. and Europe [23 ,32].…”
Section: Molecular Epidemiology Of Ca-mrsamentioning
confidence: 99%
“…There has been no systematic analysis of ciprofloxacin resistance associated with particular genetic back grounds or diseases [10]. This study involves ciprofloxacin resistant MRSA and MSSA isolates, their genetic backgrounds and mutations important in causing the resistance as we have analyzed the clonal complexes present among Indian S. aureus isolates in an earlier study [11]. ST772 (single locus variant of ST1) is one of the prominent sequence types present among Indian community associated S. aureus, and there is not much information on resistance to this antibiotic and its mechanism [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This study involves ciprofloxacin resistant MRSA and MSSA isolates, their genetic backgrounds and mutations important in causing the resistance as we have analyzed the clonal complexes present among Indian S. aureus isolates in an earlier study [11]. ST772 (single locus variant of ST1) is one of the prominent sequence types present among Indian community associated S. aureus, and there is not much information on resistance to this antibiotic and its mechanism [11][12][13]. This work demonstrates that a high percentage of patients in this tertiary care hospital carry CA-MRSA which is highly resistant to ciprofloxacin and a single mutation in gyrA gene is responsible for high resistance in ST772.…”
Section: Introductionmentioning
confidence: 99%